Efektivitas Penyuluhan Pemeriksaan Sadari Terhadap Peningkatan Pengetahuan Siswi di SMA N 1 Barru Tahun 2020 - Masita, Syarifah (Jurnal Ilmiah Amanah Akademika, 2020)
Breast cancer is the second leading cause of death for women after cervical cancer. Education health about breast examination will increase the knowledge of young women so that it will improve their health status. Wrong one goal of the effort breast cancer prevention namely young women. , cancer Breasts take first place in hospitalized patients throughout Indonesia (16.85%) followed by cancer birth neck (11.78%). The highest cancer suffered by Indonesian women is breast cancer with an incidence of 26 per 100,000 women. This study aims to see the effectiveness of counseling about SADARI in increasing the knowledge of young women using the Combain method, which is a combination of R&D and Quasi Experiments. The research process was carried out using the Pre-test-Intervention-Post test to get the desired results. The results of this study indicate that there were changes during the Pre-test and Post Test, which means that there was an increase in knowledge after giving counseling about SADARI to Respondents. Counseling is an effective medium in increasing one's knowledge and growing self-awareness about the importance of SADARI.